The Role of Ownership in Increasing Firm Value of Manufacturing Industry in Indonesia - Handriani, Eka (Jurnal Organisasi dan Manajemen, 2020)
This study examines the effect of the independent commissioner’s composition, audit committee, firm size, and profitability toward the value of manufacturing companies listed in the Indonesia Stock Exchange. The population of this research is manufacturing companies listed in the Indonesia Stock Exchange (IDX) from 2013-2015 that reported a complete annual report and published in the Indonesian Capital Market Directory. Researchers used a purposive sampling method and employed 208 companies as samples, and data processing in the study used multiple linear regression. Findings. This study find that the independent commissioner’s composition and Audit Committee has no significant effect on firm value. Finding also shows that firm size and profitability has a positive significant effect on firm value. Based on those findings, investors have to use financial information, especially financial reports, as information for long-term investment decisions. The finding may be useful for the listed companies in Indonesia Stock Exchange since they must know their size and profitability, and those variables are important to enhance their value.